Comparison of nutritional screening parameters in oncology patients with malnutrition: handgrip strength as a reliable parameter - Galata, Christian; Arensmeyer, Jan; Hetjens, Svetlana; Seyfried, Steffen; Vassilev, Georgi; Otto, Mirko (Progress in Nutrition, 2019)
Aim: To evaluate handgrip strength (HGS), phase angle (PA), serum albumin, nutritional risk screening (NRS) and quality of life (QoL) as markers for nutritional status and prognostic factors for survival in oncology patients with malnutrition and parenteral nutritional therapy. Methods: We conducted a prospective study with 36 patients between August 2013 and November 2015. HGS was measured using a hydraulic dynamometer, PA was calculated based on bioelectrical impedance tests. Serum albumin levels were measured and a nutritional risk screening (NRS 2002) was performed. The Short Form 12 (SF-12) questionnaire was used to assess QoL. PA was regarded as the gold standard for determining body composition and nutritional status. A 1-year follow-up was performed, and patient survival was evaluated. Results: HGS showed a significant correlation with PA in bioelectrical impedance analysis. Body mass index (BMI) was not correlated with HGS. Albumin and NRS showed poor specificity as compared to PA. QoL was not correlated with parameters for nutritional status. Overall survival was poor with a 1-year survival rate of 15%. Conclusions: Compared to serum albumin and BMI, HGS is a reliable tool for the assessment of nutritional status in oncology patients. When indication for parenteral nutrition is confirmed in cancer patients with malnutrition, overall patient survival is poor.